Association of Early-Onset Spasticity and Risk for Cognitive Impairment With Mutations at Amino Acid 499 in SPAST. (April 2018) - Gillespie, Meredith K.; Humphreys, Peter; McMillan, Hugh J.; Boycott, Kym M.
Hereditary spastic paraplegia is a phenotypically and genetically heterogeneous group of neurodegenerative disorders characterized by lower extremity weakness and spasticity. Spastic paraplegia 4 (SPG4), caused by heterozygous mutations in the gene SPAST, typically causes a late-onset, uncomplicated form of hereditary spastic paraplegia in affected individuals. Additional clinical features in SPG4 have been reported on occasion, but no genotype-phenotype correlation has been established. Through targeted clinical testing, we identified 2 unrelated female patients with the same de novo p.Arg499His mutation in SPAST. Both patients presented with early-onset spasticity resulting in delayed motor milestones, which led to a diagnosis of cerebral palsy in one child and tethered cord in the other. Review of the literature identified several patients with mutations at amino acid 499 and early-onset symptoms associated with a risk of cognitive impairment. Early and accurate diagnosis of children with early-onset spasticity is important for informed prognosis and genetic counselling.